Precision measurement of ADC parameters with cumulative histogram technique using Gaussian noise. (October 2020) - Garg, Bhawana; Mishra, D.K.
Abstract: Analog to Digital Converter (ADC) is a significant part of any electronic measurement and instrumentation system. It affects the overall accuracy of the system, therefore it should be characterized and tested precisely. The ADC testing methods, available in literature use deterministic signals as stimuli and have certain limitations. This paper presents statistical testing of ADC based on the cumulative histogram technique with white Gaussian noise as stimuli. The proposed method is not much more explored in literature and shows improvement in the estimation of parameters. A large number of samples of Gaussian noise is simulated and applied to the simulated 5–10 bit ADC. The cumulative histogram is estimated, and the code transition level is calculated to obtain the transfer characteristics of ADC. The linear regression method is employed on the transfer characteristics and the best-fit line is obtained. Corrections have been applied to nullify the gain and offset error. Comparative analysis of the transfer characteristics of simulated ideal and actual ADC will lead to develop the algorithm for the estimation of static parameters Gain, offset, Integral and Differential nonlinearities, and the Effective Number of Bits. The analytical expression for the precision measurement of these parameters is derived. Simulation results are presented in support of the derived expression of the proposed method. Obtained results are compared with the results presented in the literature and hence the effectiveness of the method.